2023
DOI: 10.3390/bioengineering10040421
|View full text |Cite
|
Sign up to set email alerts
|

Socket Preservation after Tooth Extraction: Particulate Autologous Bone vs. Deproteinized Bovine Bone

Abstract: Background: The technique of socket preservation after tooth extraction allows for less volumetric decrease after tooth extraction. The aim of this retrospective study was to evaluate differences between alveolar socket preservation performed with deproteinized bovine bone graft and autologous particulate bone graft taken from the mandibular ramus. Materials and Methods: This retrospective study enrolled a total of 21 consecutive patients. A total of 11 patients underwent socket preservation with deproteinized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In contrast to a traditional approach bootstrapping does not assume any underlying distributions of the data [26]. The non-parametric bootstrap test can be used for small sample size studies [26] and is reliable for a sample of eight or greater [11], which our study exceeds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to a traditional approach bootstrapping does not assume any underlying distributions of the data [26]. The non-parametric bootstrap test can be used for small sample size studies [26] and is reliable for a sample of eight or greater [11], which our study exceeds.…”
Section: Discussionmentioning
confidence: 98%
“…Alveolar bone grafting is a technique used for bone atrophy in order to restore an adequate bone volume: autologous, heterologous and xenograft are possible materials used in this technique [9][10][11]. Alveolar bone grafting can be performed at different stages Diagnostics 2023, 13, 1642 2 of 10 in children with cleft lip and palate, with the classification based on the dentition of the patient [4].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of gingival recessions in the aesthetic zone may impact implant-supported prosthodontics after tooth extraction due to the resulting asymmetry of the implant bone level. To ensure optimal results in implant-supported prosthodontics after tooth extraction, the use of socket preservation techniques and subsequent soft tissue augmentation should be considered [ 14 , 15 , 16 ]. Gingival thickness exhibits significant variations both among individuals and within the same individual.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies have demonstrated that the coronal section of the dental extraction sockets of the buccal bone wall commonly lacks bundle bone [ 8 , 9 ]. After that, tooth extraction often leads to poor functional ability of the bundle bone [ 6 , 10 , 11 ]. It is resorbed due to osteoclastic activity, which changes the buccal crest dimensions.…”
Section: Introductionmentioning
confidence: 99%